Rekonstruksi Pendidikan Islam Sebagai Upaya Dalam Membangun Peradaban Dunia - Suyudi, M (Institut Agama Islam Riyadlotul Mujahidin Ngabar Ponorogo, 2020)
AbstractThe benchmark of progress or not a human civilization is education. An advanced and developing education will produce an advanced and developing society, both in technology and in science. Therefore, the paradigm regarding the dichotomy between religious science and general science should be dismantled and focused on a clear vision of Muslims. How to prepare future generations who are ready to face global challenges. Related to this, Islamic education which combines learning from moral, spiritual and intellectual aspects is an important part of the educational process in building world civilization. Keyword: Islamic Education, Globalization, Civilization